Synthesis and electronic device applications of two-dimensional materials - Lee, J (2019)
Since it was first demonstrated that graphene could be successfully exfoliated from a graphite flake in 2004, two-dimensional materials have emerged as one of the most promising candidate materials for future electronic and optoelectronic applications due to their unique electrical and optical properties. However, graphene has been shown to possess almost no electronic band gap, which makes it unsuitable as a channel material in transistors because it cannot be used to switch off the transistors effectively. Transition metal dichalcogenides (TMDCs), on the other hand, have recently attracted tremendous attention because certain types of TMDC monolayers such as MoS2 and WS2 have large electronic band gaps, suitable for use in electronic devices. In this thesis, chemical vapour deposition (CVD) of graphene is studied as a preliminary experiment for the subsequent growth of TMDC monolayers in order to gain an understanding of which parameters are important in the growth process. In this work, centimetre-scale graphene is successfully synthesized and a triboelectric nanogenerator is employed as a simple demonstration of an electronic application. Secondly, a thermally stable synthesis procedure for growing a uniform and large-area TMDC monolayer with large-sized single crystal grains is studied based upon a solution-processed precursor deposition technique. With this synthesis approach, the nucleation density is found to dramatically decrease because of the low supersaturation level. In addition, vertically-stacked MoS2/WS2 heterostructure devices, fabricated using this new synthetic technique, show rectifying properties and exhibit a fast photoresponse and a high photoresponsivity due to a unipolar n-n heterojunction. In the following chapter, a facile one-step CVD process for the MoS2/WS2 heterostructures and Mo1-xWxS2 alloys is demonstrated through the precise control of the timing that the precursors are introduced as well as the supersaturation level of the precursors. The heterostructures grown using this one-step method are found to have a large crystal size and a clean interface. In addition, alloyed structures are intentionally obtained in the core, the shell regions of the lateral heterostructures or over the entire region of the monolayer by controlling the relative amounts of vaporised precursors and the growth temperature. Finally, a monolayer MoS2 optoelectronic memory device using artificially-structured charge trap layers is presented. The charge trap sites lead to localized electronic states that serve as a basis for electrically-induced charge trapping and optically-mediated charge release. The optical memory devices exhibit excellent photo-responsive memory characteristics with a large linear dynamic range and a long storage lifetime. The work presented in this thesis investigates various growth strategies for synthesizing highly crystalline and large-area TMDC monolayers, and also demonstrates the realization of TMDC monolayer devices. These results provide a significant step forward in the development of future electronic and optoelectronic devices.